Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

How is sin^-1 x = cos^-1 Y is equals to. y = (1-x^2 )^ 1/2. Please explain sir

How is  sin^-1 x = cos^-1 Y  is equals to. y =  (1-x^2 )^ 1/2.    Please explain sir 

Grade:12

1 Answers

Jitender Singh IIT Delhi
askIITians Faculty 158 Points
7 years ago
Ans:
sin^{-1}(x) = cos^{-1}(y)
Let
t = cos^{-1}(y)
cos(t) = coscos^{-1}(y)
cos(t) = y
sin(t) = \sqrt{1-y^{2}}
t = sin^{-1}(\sqrt{1-y^{2}})
sin^{-1}(x) = sin^{-1}(\sqrt{1-y^{2}})
\Rightarrow x = \sqrt{1-y^{2}}
Thanks & Regards
Jitender Singh
IIT Delhi
askIITians Faculty

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free